Pengaruh Pemahaman, Sanksi Perpajakan dan Tingkat Kepercayaan Pada Pemerintah Terhadap Kepatuhan Dalam Membayar PBB-P2 - Median Wilestari; Mutiara Ramadhani (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
PBB is one of the potential sources of state revenues to continue to be explored and improved. The size of the tax revenue is determined from tax compliance in implementing the obligations in the field of taxation. This study aimed to determine the effect of perceived tax understanding, Tax Penalty and trust in government on Tax Compliance PBB in Kecamatan Kota Tangerang. The population in this study are all taxpayers PBB effective in Kecamatan Kota Tangerang. The number of samples used in this research is 95 respondents selected by spreading questionnaires. The obtained data, analyzed technique by using SEM-PLS (structural equation modeling - partial least squares) through SmartPLS 3.0 software. The research period used is 2019. The results showed that the perceived tax understanding and trust in government had a positive significant effect on Tax Compliance PBB, while Tax Penalty had no significant effect on Tax Compliance PBB in Kecamatan Kota Tangerang. Suggestions in this study is necessary to have a good quality of Tax Penalty that it will increase tax compliance PBB in Kecamatan Kota Tangerang